PENGARUH TOTAL FENOLTERIPANG PASIR (Holothuria scabra) TERHADAP RESPON IMUN NON SPESIFIK IKAN MAS (Cyprinus carpio) - Suhermanto, Achmad (Bumi Lestari, 2013)
Abstract The aim of the study was to know administration and applications of optimal doses of sea cucumber total phenol to increase nonspecific immune response of Carp. Bioactive component extraction was done by methanol and for further fractionation was dissolved with ethyl acetate (v/v). Total phenol identification on ethyl acetate fraction was done to utilize UVVis spectrophotometer and infrared. Total phenol produced was tested on carp with intraperitonial injection, the concentration of 0; 0,09; 0,18; and 0,27 mg phenols/kg fish.. Challenge be done utilizes A. hydrophila (107cell/ml) with immertion method. Statistical analysis involved one-way analysis of varians (ANOVA) by minitab 14. The level of significance were expressed as P-value less or greater than 0.05. The result of hematological parameters showed that hematocrit (PVC), hemoglobin, erythrocytes, lymphocyte pre infection was increased significantly and post-bacterial was decreased significantly (p<0.05). Leukocytes, Neutrophils pre-and post-infection were significantly increased (p<0.05). Eosinophils, monocytes pre-and post bacterial infection were not differ significantly between treatment (p<0.05).
Keywords: Key Words :Holothuria scabra, Cyprinus carpio, Aeromonas hydrophila, nonspecific immune response